Training needs of the front-line extension workers in the Western Development Region of Nepal - Pradhan, Komal Prasad (1985)
The main purpose of this study its to determine the training needs of the front-line extension workers (FLEWs) in the western Development Region of Nepal. The specific objectives of this study were to determine: the importance of some selected professional competencies in the fields of extension, communication and social skills in relation to FLEWs' job performance and for inclusion in the in-service training programmes: the differences in the respondents' perceptions on the importance of the professional competency categories in relation to their job performance and for inclusion in the in service training programmers when the respondents were grouped according to staff position, age, tenure, educational level and attendance in in-service training programmers and: the relationships between the importance of the professional Competency categories in relation to FLEWs' job performance and their importance for inclusion in the in-service training programmers.